Effect of Reduced Rate of Post Emergence Herbicide with Aqueous Extracts of Lentil Crop Residues on Weed Management Indices and Yield of Transplanted Aman Rice (Journal of the Bangladesh Agricultural University, 2025)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, from July to December 2023, to assess the effectiveness of integrating reduced doses of post-emergence herbicides with aqueous extracts of lentil crop residues on weed management indices and the yield of T. aman rice. The experimental design included two factors: rice variety (BRRI dhan49, BRRI dhan87, and Binadhan-7) and herbicide treatments combined with aqueous extracts of lentil residues (control, recommended dose of herbicide, various reduced herbicide doses plus extracts, and weed-free). The study followed a randomized complete block design with three replications. The results indicated that weed population, dry weight, and various weed management indices, such as Weed Control Index (WCI), Weed Control Efficiency (WCE), and Weed Index (WI), were significantly influenced by both variety and the use of crop residue extracts. The highest weed growth was observed in the Binadhan-7 variety, with the lowest in BRRI dhan87. The control treatment exhibited the highest weed growth, while the lowest was found in the weed-free treatment and the 80% recommended dose of post-emergence herbicide with lentil residue extract. The weed-free treatment achieved the highest WCI and WCE values, indicating superior weed control. In contrast, the lowest weed management indices were recorded in the weed free treatment. Grain yield (GY) was highest in BRRI dhan87 (5.34 t ha-1) and lowest in BRRI dhan49 (4.51 t ha-1). The maximum yield (5.83 t ha-1) was observed in the weed-free treatment, followed by the T4 treatment (5.40 t ha-1). The lowest GY (2.65 t ha-1) was found in the control. Thus, integrating 80% of the recommended herbicide dose with lentil residue extract is suggested for effective weed control and higher yield in transplanted aman rice.J Bangladesh Agril Univ 23(2): 113-128, 2025